Factors associated with longitudinal change of meniscal extrusion in overweight women without clinical signs of osteoarthritis. (10th March 2021) - van der Voet, Jan A; Wesselius, Daan; Zhang, Fan; Vroegindeweij, Dammis; Oei, Edwin H; Bierma-Zeinstra, Sita M A; Englund, Martin; Runhaar, Jos
Abstract: Objectives: To identify variables associated with longitudinal change in meniscal extrusion, which might be used as possible targets for knee osteoarthritis (KOA) prevention. Methods: In a high-risk population of middle-aged overweight women, meniscal extrusion was assessed with magnetic resonance imaging (1.5 T, coronal proton density, in-plane resolution 0.5 mm 2, Sante DICOM Editor) at baseline and after 30 months. Outcomes were the absolute change in medial and lateral extrusion (mm) and relative change in extrusion (%). Based upon literature, 11 factors were hypothesized to be associated with longitudinal change. Generalized estimating equations were used to model the effect on meniscal change ( P <0.05). Results: In total, 677 knees of 343 women were available for analysis, with a mean age of 55.7 years (+/−3.2) and a mean BMI of 32.3 kg/m 2 (+/−4.2). The greatest change in meniscal extrusion appeared medially with incident meniscal tear (4.4%; absolute 0.9 mm (95% CI: 0.3, 1.5; P =0.004); relative 14.5% (4.4, 24.7; 0.005)). Varus malalignment was associated with an increase of medial extrusion of 0.6 mm (37.6%; 0.1, 1.0; 0.009). A 5 kg/m 2 higher baseline BMI was associated with absolute and relative increase of medial extrusion of 0.2 mm and 2.96% (0.1, 0.3; <0.001 and 1.3, 4.8; 0.002). Less explicit but significant changes in extrusion appeared with longitudinal change in BMI. Conclusion: Meniscal tears, varus malalignment and BMI were significantly associated with change in meniscal extrusion in middle-aged overweight women, providing viable therapeutic targets to prevent or reduce extrusion and thereby decelerate KOA development.